1993
DOI: 10.1111/j.1365-3032.1993.tb00461.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of drone age, semen storage and contamination on semen quality in the honey bee (Apis mellifera)

Abstract: Abstract. The effect of semen storage time, drone age and semen contamination on honey bee semen quality was investigated using assays for motility and viability of semen in vitro. Four age groups (1, 2, 4 and 6 weeks) and five storage times (0, 1, 2, 4 and 6 weeks) were examined. As storage time increased, sperm viability and motility significantly decreased. However, motility patterns of unstored semen samples were significantly lower than those samples that were stored up to 2 weeks. Sperm viability decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
1
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 21 publications
3
42
1
1
Order By: Relevance
“…Almeida and Soares (2002) observed no significant mortality of semen diluted with green coconut water and held for two weeks. Locke and Peng (1993) reported an initial viability of 87% dropped to 78% after 6 weeks of storage. Collins (2000b) reported 70% to 80% viability of semen diluted with Tris buffer and held at room temperature, 25…”
Section: Affects Of Semen Handling and Storagementioning
confidence: 99%
See 1 more Smart Citation
“…Almeida and Soares (2002) observed no significant mortality of semen diluted with green coconut water and held for two weeks. Locke and Peng (1993) reported an initial viability of 87% dropped to 78% after 6 weeks of storage. Collins (2000b) reported 70% to 80% viability of semen diluted with Tris buffer and held at room temperature, 25…”
Section: Affects Of Semen Handling and Storagementioning
confidence: 99%
“…• C (Harbo and Williams, 1987;Locke and Peng, 1993;Konopacka and Bienkowska, 1995). Temperatures below10…”
Section: Affects Of Semen Handling and Storagementioning
confidence: 99%
“…Various assays were used to evaluate the success of the storage includ-More recent research raises the possibility that previous assessments of storage success may be misleading. Stains that directly assess viability of the spermatozoa have now been applied to the honey bee [3,14,17]. Use of such stains indicated that lack of motility was not necessarily an indication of dead spermatozoa [15], nor did presence in the spermatheca ensure that a spermatozoan was living (pers.…”
Section: Introductionmentioning
confidence: 99%
“…The same was found for the harvester ant Pogonomyrmex occidentalis (Wiernasz and Cole, 2003). Queen and male age is also important for AI success in the honeybee Apis mellifera, where decades of bee breeding have shown that more queens survive and successfully produce offspring when they are inseminated roughly 7-10 days after hatching (Cobey, 2007) and using the semen of males that are about 2-weeks old, when semen quality is highest (Locke and Peng, 1993). We obtained further indications of the importance of optimal starting material by scrutinizing the fire ant AI data by Ball et al (1983).…”
Section: Discussionmentioning
confidence: 54%